Concise guide to pediatric arrhythmias - Wren, C. (Christopher) (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2012)
This book provides a practical guide to diagnosis and treatment of arrhythmias in children for pediatricians and general pediatric cardiologists. Using multiple ECG examples, the author provides concise descriptions of the key features of each arrhythmia to help the clinician make a diagnosis.
Front Matter -- Anatomy, Physiology, and Epidemiology of Arrhythmias -- ECGs and Other Recording Devices -- Other Diagnostic Techniques -- The Normal ECG and Variants -- Interpretation of the ECG in Tachycardia -- Adenosine in the Diagnosis of Tachycardias -- Atrial Tachycardia -- Multifocal Atrial Tachycardia -- Atrial Flutter -- Atrial Fibrillation -- Atrial Premature Beats -- Atrioventricular Re-Entry Tachycardia -- Wolff-Parkinson-White Syndrome -- Permanent Junctional Reciprocating Tachycardia -- Atriofascicular Re-Entry Tachycardia -- Atrioventricular Nodal Re-Entry Tachycardia -- Junctional Ectopic Tachycardia -- Ventricular Tachycardia -- Neonatal Ventricular Tachycardia -- Incessant Idiopathic Infant Ventricular Tachycardia -- Idiopathic Left Ventricular Tachycardia -- Idiopathic Right Ventricular Tachycardia -- Ventricular Premature Beats -- Ventricular Fibrillation -- Long QT Syndrome -- Catecholaminergic Polymorphic Ventricular Tachycardia -- Brugada Syndrome -- First- and Second-Degree Atrioventricular Block -- Complete Atrioventricular Block -- Sinus Node Dysfunction and Sinoatrial Disease -- Early Postoperative Arrhythmias -- Late Postoperative Arrhythmias -- Arrhythmias in Congenital Heart Defects -- Arrhythmias in Cardiomyopathies -- Syncope -- Sudden Death -- Antiarrhythmic Drug Treatment -- Pacemakers and Implantable Defibrillators -- Catheter Ablation -- Artifacts -- Appendix.
Includes bibliographical references and index.
Print version record.
Keywords: Arrhythmia in children -- Handbooks, manuals, etc; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Arrhythmia in children; Electronic books; Handbooks and manuals; Electronic books